Metal-containing taurine compounds protect rat's brain in reperfusion-induced injury - Elena V. Semeleva; Ekaterina V. Blinova; Andrey V. Zaborovsky; Irina A. Gromova; Asliddin S. Shukurov; Dmitry S. Blinov; Egor A. Turovsky; Olga V. Vasilkina; Elena G. Lobanova; Elena A. Samishina; Yan A. Mazov; Alexey I. Sokolov; et al. (Belgorod National Research University, 2020)
Introduction: The study aim was to explore a neuroprotective action of magnesium (LKhT-317) and zinc (LKhT-318) taurine salts on experimental models of reperfusion brain damage in rats and cell culture. Materials and methods: The study was performed on male Sprague Dawley rats, and rat's hippocampal mixed neuroglial cell culture. Magnesium- (LKhT-317) and zinc-containing (LKhT-318) derivatives of taurine were studied. Reperfusion brain damage was induced 30 min after intraluminal cerebral middle artery occlusion. Severity of the injury was assessed by local blood flowmetry, neurological symptoms scaling and brain tissue staining. Levels of IL-1b, IL-10 and TNF-alpha in tissue were determined by qualitative ELISA. Caspase-3 and Bcl-2 expressions were detected by IHC. Neurons survival was assessed by cytochemistry. Cellular calcium responses were detected by fluorescent microscopy of Fura-2-containig cells. Results and discussion: Metal-containing taurine derivatives - LKhT-317 and LKhT-318 - demonstrated a sufficient neuroprotective property in rats with a reperfusion-induced brain injury. Both derivatives effectively prevented severity of the animals' brain damage, motor deficiency, reduction of microvascular perfusion, and proinflammatory cytokines production. Magnesium-containing compound LKhT-317 was comparatively more effective than zinc-containing one. LKhT-317 possessed an anti-apoptotic action in vivo, and protected neurons from OGD-mediated cell death in mixed hippocampal culture. The aforementioned actions may be associated with an LKhT-317 inhibitory effect on NMDA-induced cellular Ca2+ response and, therefore, the anti-excitotoxic property of the compound. Conclusion: Magnesium- and zinc-containing taurine derivatives may be considered as promising neuroprotectors in the reperfusion-induced brain injury.